Polyester resin for sand streak powder coating and preparation method thereof
By combining the polyester resin formula of soft-segment polyurethane and hard-segment polyester resin, the problem of hydrolysis of polyester resin after boiling test is solved, the water resistance and mechanical properties of the powder coating of aluminum profiles are improved, and the weather resistance is formed is good. Sand-grain powder coating, suitable for surface treatment of aluminum profiles.
Patent Information
- Application Number
- CN202411419743.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-12
Smart Images

Figure BDA0005080422960000081 
Figure BDA0005080422960000091 
Figure BDA0005080422960000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a polyester resin for sand-texture powder coating and a preparation method thereof. Background Art
[0002] Aluminum profiles have the characteristics of low density, light weight and good mechanical properties, and are widely used in the construction field. However, aluminum profiles without surface treatment have a simple appearance and are easily corroded in humid atmospheres, making it difficult to meet the requirements of high decorativeness and strong weather resistance of building materials. In order to improve the decorative effect, enhance corrosion resistance and extend the service life, aluminum profiles generally need to be surface treated. Surface treatment technology can be divided into three categories: anodizing, anodizing-electrophoresis, and organic coating. Among them, organic coating treatment includes powder spraying and fluorocarbon spraying. Because powder coating is strong and durable, has good chemical resistance, and is simple to produce, it accounts for a large proportion in aluminum profile surface treatment.
[0003] Sand-textured powder coatings can scatter light, giving people a comfortable look. They also have the advantages of high film hardness, smooth feel, not easy to scratch, and aging resistance. They are widely used in the field of architectural aluminum profiles. Since aluminum profiles are mostly used in outdoor environments, powder coatings in this field have high performance requirements for polyester resins, requiring both product economy, weather resistance, and water resistance. Aluminum profiles are easily corroded in humid atmospheres, so the water resistance of powder coatings is the performance that application companies pay the most attention to.
[0004] At present, the water resistance test of powder coatings usually uses the pressure cooker boiling test method in the GB / T 5237.4-2004 standard. The water resistance of the coating is judged by the gloss retention rate, color difference and water spot coverage of the powder coating before and after boiling, which is generally also called boiling resistance. Polyester resin contains a large number of ester bonds in its structure, which are prone to hydrolysis under the action of water, resulting in ester bond breakage, reduced coating density, and affecting the performance of the coating. At present, the color difference ΔE of sand-textured coatings is generally around 2.0. After boiling, visual inspection has shown that the color has changed, and the overall performance of the coating has decreased. At the same time, since the density of the coating is reduced after boiling, it is easier to absorb and contain water, causing "water spots" on the surface of the coating, which seriously affects the appearance of the coating.
[0005] CN 108264828 A discloses a method for preparing a polyester resin for aluminum profile powder coating. The formula uses special monomers such as p-phenylenediamine and silicone oil to improve the water boiling resistance of the coating. However, the powder coating prepared by the resin is a leveling type. The surface of the aluminum profile coated with the leveling powder is easily scratched and discolored during transportation and use. Therefore, the leveling powder for aluminum profiles is becoming more and more a non-mainstream product. CN 103483988 A discloses a water boiling resistant sand grain powder coating suitable for powdering the edges and corners of aluminum profiles and a preparation method thereof. The method improves the water resistance of the sand grain powder coating on the aluminum profile by adding a gas phase oxide filler such as aluminum oxide and silicon dioxide during the preparation of the powder coating. However, the patent focuses more on the preparation of the powder coating and lacks research and introduction on polyester resins. CN 114410196 A discloses a water-boiling resistant powder coating and its preparation method and application. By adding water-resistant fillers and water-resistant additives to the powder coating, the requirements of water-boiling resistance and scratch resistance of the coating are met, so that the wheel hub can adapt to high temperature and rainy environments, but the polyester resin is not studied. CN117229485 A discloses a copolymer resin for anti-shrinkage, anti-blooming and water-boiling resistant powder coating and its preparation method. The copolymer resin is finally obtained by melting and adding acrylic resin to the polyester resin. The addition of acrylic resin improves the water-boiling resistance and anti-blooming performance of the coating, but does not involve the modification of the polyester resin structure. At the same time, the addition of acrylic resin will affect the mechanical properties of the coating. Summary of the invention
[0006] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a polyester resin for sand-textured powder coating; the second purpose of the present invention is to provide a method for preparing the polyester resin for sand-textured powder coating; the third purpose of the present invention is to provide a sand-textured powder coating; the fourth purpose of the present invention is to provide a coating; the fifth purpose of the present invention is to provide a polyester resin for sand-textured powder coating, or the application of sand-textured powder coating.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a polyester resin for sand-textured powder coating, comprising the following raw materials: a soft segment polyurethane, a hard segment polyester resin and a silane coupling agent; in terms of mass percentage, the soft segment polyurethane comprises the following raw materials: 5-20% polyisocyanate and 80-95% oligomer polyol; the hard segment polyester resin comprises the following raw materials: 30-45% aliphatic polyol and 60-75% polyacid.
[0009] Preferably, the soft segment polyurethane comprises the following preparation raw materials by mass percentage: 5-15% polyisocyanate and 85-95% oligomer polyol.
[0010] Preferably, the hard segment polyester resin comprises the following preparation raw materials, by mass percentage: 35-40% aliphatic polyol, 60-65% polyacid.
[0011] Preferably, the acid value of the hard segment polyester resin is 5-25 mgKOH / g; further preferably, the acid value of the hard segment polyester resin is 7-20 mgKOH / g; further preferably, the acid value of the hard segment polyester resin is 7-5 mgKOH / g.
[0012] Preferably, the viscosity of the hard segment polyester resin at 200°C is 300-3000 mPa·s; further preferably, the viscosity of the hard segment polyester resin at 200°C is 500-2500 mPa·s; further preferably, the viscosity of the hard segment polyester resin at 200°C is 500-2000 mPa·s.
[0013] Preferably, the polyisocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate (HDI), dicyclohexylmethane diisocyanate (HMDI), isophorone diisocyanate, and p-phenylene diisocyanate.
[0014] Preferably, the molecular weight of the oligomer polyol is 300-5000 g / mol; further preferably, the molecular weight of the oligomer polyol is 500-3000 g / mol.
[0015] Preferably, the oligomer polyol includes at least one of polyester polyol, polyether polyol and polyolefin polyol.
[0016] Preferably, the polyester polyol includes at least one of polyethylene adipate (PEA), polycarbonate diol (PCDL), and polycaprolactone diol.
[0017] Preferably, the polyether polyol includes at least one of polytetramethylene glycol (PTMG), polyoxypropylene glycol, and polymer polyol.
[0018] Preferably, the polyolefin polyol includes at least one of hydroxyl-terminated polybutadiene styrene (HTBS), hydroxyl-terminated polybutadiene acrylonitrile, and hydroxyl-terminated polybutadiene.
[0019] Preferably, the aliphatic polyol includes at least one of neopentyl glycol, ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol, hexylene glycol, diethylene glycol, 1,4-cyclohexanediol, 2-methyl-2,4-pentanediol, ethyl butyl propanediol, trimethylolpropane, and pentaerythritol.
[0020] Preferably, the polyacid includes at least one of terephthalic acid, isophthalic acid, trimellitic anhydride, succinic acid, adipic acid, and 1,4-cyclohexane diacid.
[0021] Preferably, the silane coupling agent includes at least one of bis[3-(triethoxysilyl)propyl]amine and N-[3-(trimethoxysilyl)propyl]ethylenediamine.
[0022] Preferably, the polyester resin for sand-textured powder coating further comprises the following preparation raw materials: an acidolysis agent, a curing accelerator, and an antioxidant.
[0023] Preferably, the acidolysis agent includes at least one of terephthalic acid, isophthalic acid, trimellitic anhydride, succinic acid, adipic acid, and 1,4-cyclohexane diacid.
[0024] Preferably, the curing accelerator includes at least one of triphenylethylphosphonium bromide and benzyltributylammonium chloride.
[0025] Preferably, the antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant.
[0026] Preferably, the hindered phenol antioxidant includes at least one of 2,6-di-tert-butyl-p-methylphenol (BHT), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1076), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine (antioxidant 1098), and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] (antioxidant 245); further preferably, the hindered phenol antioxidant is antioxidant 1010.
[0027] Preferably, the phosphite antioxidant includes at least one of diphenyl isooctyl phosphite (ODPP), tris[2.4-di-tert-butylphenyl]phosphite (antioxidant 168), bisphenol A phosphite, and triphenyl phosphite (TPP); further preferably, the phosphite antioxidant is antioxidant 168.
[0028] Preferably, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:(0.5-1.5); further preferably, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:(0.8-1.2).
[0029] Preferably, the polyester resin for sand-textured powder coating comprises the following raw materials, measured by mass percentage: 1-10% soft segment polyurethane, 80-90% hard segment polyester resin, 0.1-2% silane coupling agent, 1-10% acidolysis agent, 0.01-0.5% curing accelerator, and 0.1-2% antioxidant; further preferably, the polyester resin for sand-textured powder coating comprises the following raw materials: 4-10% soft segment polyurethane, 85-90% hard segment polyester resin, 0.1-1% silane coupling agent, 3-8% acidolysis agent, 0.01-0.1% curing accelerator, and 0.1-1% antioxidant.
[0030] Preferably, the acid value of the polyester resin for sand-textured powder coating is 25-40 mgKOH / g; further preferably, the acid value of the polyester resin for sand-textured powder coating is 30-40 mgKOH / g.
[0031] Preferably, the viscosity of the polyester resin for sand-textured powder coating at 200°C is 3000-11000 mPa·s; further preferably, the viscosity of the polyester resin for sand-textured powder coating at 200°C is 5000-11000 mPa·s; even more preferably, the viscosity of the polyester resin for sand-textured powder coating at 200°C is 7000-10000 mPa·s.
[0032] The second aspect of the present invention provides a method for preparing the polyester resin for sand-textured powder coating according to the first aspect of the present invention, comprising the following steps:
[0033] S1, polyisocyanate and oligomer polyol are polymerized to obtain soft segment polyurethane, and aliphatic polyol and polyacid are condensed to obtain hard segment polyester resin;
[0034] S2, mixing the soft segment polyurethane and the hard segment polyester resin for reaction, adding an acidolysis agent, performing vacuum polycondensation reaction, adding a curing accelerator, an antioxidant and a silane coupling agent, and obtaining the polyester resin for sand texture powder coating.
[0035] Preferably, in step S1, the process of preparing the soft segment polyurethane and the hard segment polyester resin further comprises using catalysts respectively.
[0036] Preferably, the catalyst is independently selected from at least one of monobutyltin oxide, dibutyltin dilaurate, monobutyltin triisooctoate, ethyl titanate, butyl titanate, polytitanate, and titanate chelate.
[0037] Preferably, the polyisocyanate and oligomer polyol are polymerized to prepare soft segment polyurethane, and the amount of the catalyst used is 0.1-0.3% of the total mass of the materials; further preferably, the amount of the catalyst used is 0.1-0.2% of the total mass of the materials.
[0038] Preferably, the aliphatic polyol and polyacid ester are polycondensed to prepare the hard segment polyester resin, and the amount of the catalyst used is 0.05-0.1% of the total mass of the material; further preferably, the amount of the catalyst used is 0.06-0.08% of the total mass of the material.
[0039] Preferably, in step S1, the polymerization reaction temperature of the soft segment polyurethane is 25-120°C; further preferably, the polymerization reaction temperature of the soft segment polyurethane is 50-110°C; further preferably, the polymerization reaction temperature of the soft segment polyurethane is 70-100°C.
[0040] Preferably, in the step S1, the polymerization reaction time of the soft segment polyurethane is 0.5-3 h; further preferably, the polymerization reaction time of the soft segment polyurethane is 0.5-2 h.
[0041] Preferably, in step S1, the esterification polycondensation reaction temperature of the hard segment polyester resin is 25-250°C; further preferably, the esterification polycondensation reaction temperature of the hard segment polyester resin is 130-245°C; further preferably, the esterification polycondensation reaction temperature of the hard segment polyester resin is 180-245°C.
[0042] Preferably, in the step S1, the esterification polycondensation reaction time of the hard segment polyester resin is 5-16 hours; further preferably, the esterification polycondensation reaction time of the hard segment polyester resin is 10-16 hours.
[0043] Preferably, in step S2, the mixing reaction of the soft segment polyurethane and the hard segment polyester resin further comprises using a catalyst.
[0044] Preferably, the catalyst includes at least one of monobutyltin oxide, dibutyltin dilaurate, monobutyltin triisooctoate, ethyl titanate, butyl titanate, polytitanate, and titanate chelate.
[0045] Preferably, in step S2, the mixing reaction temperature of the soft segment polyurethane and the hard segment polyester resin is 150-200°C; further preferably, the mixing reaction temperature of the soft segment polyurethane and the hard segment polyester resin is 165-200°C.
[0046] Preferably, in step S2, the mixing reaction time of the soft segment polyurethane and the hard segment polyester resin is 0.5-3 h; further preferably, the mixing reaction time of the soft segment polyurethane and the hard segment polyester resin is 0.5-2 h.
[0047] Preferably, in step S2, the reaction temperature after adding the acidolysis agent is 180-240°C; further preferably, the reaction temperature after adding the acidolysis agent is 200-235°C.
[0048] Preferably, in step S2, the reaction time after adding the acidolysis agent is 1-5 h; further preferably, the reaction time after adding the acidolysis agent is 2-4 h.
[0049] Preferably, in step S2, the pressure of the vacuum polycondensation reaction is 0.08-0.1 MPa; further preferably, the pressure of the vacuum polycondensation reaction is 0.09-0.1 MPa.
[0050] Preferably, in step S2, the vacuum polycondensation reaction time is 0.5-2 h; further preferably, the vacuum polycondensation reaction time is 1-2 h.
[0051] The third aspect of the present invention provides a sand-textured powder coating, comprising the polyester resin for sand-textured powder coating according to the first aspect of the present invention; the mass percentage of the polyester resin for sand-textured powder coating is 50-60%.
[0052] Preferably, the mass percentage of the polyester resin for the sand-texture powder coating is 55-60%.
[0053] Preferably, the sand-textured powder coating further comprises the following raw materials, measured by mass percentage: 2-8% curing agent, 35-45% inorganic filler, 0.1-1% sand-textured agent, 0.1-1% bentonite, and 0.3-2% carbon black; further preferably, the sand-textured powder coating further comprises the following raw materials, measured by mass percentage: 2-6% curing agent, 36-42% inorganic filler, 0.1-0.5% sand-textured agent, 0.1-0.5% bentonite, and 0.3-1% carbon black.
[0054] Preferably, the curing agent includes at least one of triglycidyl isocyanurate (TGIC), triglycidyl trimellitate (PT910), triglycidyl trimellitate (Aplus101), and β-hydroxyalkylamide (HAA); more preferably, the curing agent is triglycidyl isocyanurate (TGIC).
[0055] Preferably, the inorganic filler comprises barium sulfate.
[0056] Preferably, the sand-textured powder coating is prepared by a method comprising the following steps: mixing various raw materials, tableting with a twin-screw extruder, freeze-crushing, and sieving to obtain the sand-textured powder coating.
[0057] The fourth aspect of the present invention provides a coating formed by the sand-textured powder coating according to the third aspect of the present invention.
[0058] Preferably, during the coating formation process, the curing temperature of the sand-textured powder coating is 150-170°C; further preferably, the curing temperature of the sand-textured powder coating is 155-165°C.
[0059] Preferably, during the coating formation process, the curing time of the sand-textured powder coating is 5-20 minutes; further preferably, the curing time of the sand-textured powder coating is 10-20 minutes.
[0060] Preferably, the 60° gloss of the coating is 7-10%; more preferably, the 60° gloss of the coating is 8-9%.
[0061] The fifth aspect of the present invention provides the use of the polyester resin for sand-textured powder coating according to the first aspect of the present invention, or the sand-textured powder coating according to the third aspect of the present invention in the surface treatment of aluminum profiles.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] 1) The polyester resin for sand-textured powder coating provided by the present invention combines a soft segment polyurethane structure containing an oligomer polyol and a hard segment polyester resin structure, has an acid value of 25-40 mgKOH / g, a viscosity of 3000-11000 mPa·s at 200° C., and a glass transition temperature of 65-75° C. The acid value, viscosity and glass transition temperature are suitable. When used as a raw material for preparing powder coating, it is beneficial to improve the performance of the coating.
[0064] 2) The method for preparing the polyester resin for sand-texture powder coating provided by the present invention has simple steps and is suitable for industrial use.
[0065] 3) The sand-textured powder coating provided by the present invention is added with the polyester resin for sand-textured powder coating provided by the present invention. The sand-textured powder coating forms a black sand-textured coating under the curing condition of 160°C / 15min, and has excellent water boiling resistance and sanding effect. After the coating is boiled in high-pressure water at 120°C for 2h, the gloss retention rate is ≥94%, the color difference ΔE≤2, and basically no water spots appear on the board surface; the 60° gloss of the coating is less than 9%, the gloss is low, and the mechanical properties are excellent. When applied to the surface treatment of aluminum profiles, the coating has good water resistance, is not easy to be corroded, is not easy to be scratched, can maintain excellent performance for a long time, and will not affect the appearance effect. DETAILED DESCRIPTION
[0066] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0067] Example 1
[0068] This embodiment provides a soft segment polyurethane, and the preparation steps are as follows:
[0069] 500g of polycarbonate diol (PCDL2000) was added to a four-necked flask, and a stirring device and a vacuum device for reduced pressure distillation were set up on the four-necked flask. After the vacuum degree of the four-necked flask was reduced to -0.99MPa, the temperature of the oil bath was adjusted to 120°C, and the high temperature was removed for 1h. Subsequently, the four-necked flask was cooled to 70°C, 65g of dicyclohexylmethane diisocyanate (HMDI) and 0.56g of dibutyltin dilaurate were added to the four-necked flask, and nitrogen was introduced into the four-necked flask. After HMDI was dissolved, the temperature was raised to 85°C, and it was fully stirred for 1.5h to obtain soft segment polyurethane R1.
[0070] Example 2
[0071] This embodiment provides a soft segment polyurethane, and the preparation steps are as follows:
[0072] 500g of polyethylene adipate (PEA2000) was added to a four-necked flask, and a stirring device and a vacuum device for reduced pressure distillation were set up on the four-necked flask. After the vacuum degree of the four-necked flask was reduced to -0.99MPa, the temperature of the oil bath was adjusted to 120°C, and the high temperature was removed for 1h. Subsequently, the four-necked flask was cooled to 70°C, 65g of dicyclohexylmethane diisocyanate (HMDI) and 0.56g of dibutyltin dilaurate were added to the four-necked flask, and nitrogen was introduced into the four-necked flask. After HMDI was dissolved, the temperature was raised to 85°C, and it was fully stirred for 1.5h to obtain soft segment polyurethane R2.
[0073] Example 3
[0074] This embodiment provides a soft segment polyurethane, and the preparation steps are as follows:
[0075] 500g of polytetrahydrofuran ether diol (PTMG2000) was added to a four-necked flask, and a stirring device and a vacuum device for reduced pressure distillation were set up on the four-necked flask. After the vacuum degree of the four-necked flask was reduced to -0.99MPa, the temperature of the oil bath was adjusted to 120°C, and the high temperature was removed for 1h. Subsequently, the four-necked flask was cooled to 70°C, 65g of dicyclohexylmethane diisocyanate (HMDI) and 0.56g of dibutyltin dilaurate were added to the four-necked flask, and nitrogen was introduced into the four-necked flask. After HMDI was dissolved, the temperature was raised to 85°C, and it was fully stirred for 1.5h to obtain soft segment polyurethane R3.
[0076] Example 4
[0077] This embodiment provides a soft segment polyurethane, and the preparation steps are as follows:
[0078] 500g of hydroxy-terminated polybutadiene styrene (HTBS2000) was added to a four-necked flask, and a stirring device and a vacuum device for reduced pressure distillation were set up on the four-necked flask. After the vacuum degree of the four-necked flask was reduced to -0.99MPa, the temperature of the oil bath was adjusted to 120°C, and the high temperature was removed for 1h. Subsequently, the four-necked flask was cooled to 70°C, 65g of dicyclohexylmethane diisocyanate (HMDI) and 0.56g of dibutyltin dilaurate were added to the four-necked flask, and nitrogen was introduced into the four-necked flask. After HMDI was dissolved, the temperature was raised to 85°C, and it was fully stirred for 1.5h to obtain soft segment polyurethane R4.
[0079] Example 5
[0080] This embodiment provides a soft segment polyurethane, and the preparation steps are as follows:
[0081] 500g of polycarbonate diol (PCDL2000) was added to a four-necked flask, and a stirring device and a vacuum device for reduced pressure distillation were set up on the four-necked flask. After the vacuum degree of the four-necked flask was reduced to -0.99MPa, the temperature of the oil bath was adjusted to 120℃, and high-temperature dehydration was performed for 1h. Subsequently, the four-necked flask was cooled to 70℃, 42g of hexamethylene diisocyanate (HDI) and 0.54g of dibutyltin dilaurate were added to the four-necked flask, and nitrogen was introduced into the four-necked flask. After HDI was dissolved, the temperature was raised to 85℃, and it was fully stirred for 1.5h to obtain soft segment polyurethane R5.
[0082] Example 6
[0083] This embodiment provides a hard segment polyester resin, and the preparation steps are as follows:
[0084] 271 g of neopentyl glycol, 62 g of ethylene glycol, 16 g of trimethylolpropane, 597 g of terephthalic acid and 0.8 g of monobutyltin oxide were added into a four-necked flask, and a stirring device, a distillation column and a condensation column were set up on the four-necked flask. In a nitrogen atmosphere, the temperature was raised to 240°C at a heating rate of 5°C / h. After reaching the set temperature, the temperature was kept for 4 hours. The sampled resin was clear and bright, with an acid value of 7.5 mgKOH / g and a viscosity of 1200 mPa·s, to obtain a hard segment polyester resin H1.
[0085] Example 7
[0086] This embodiment provides a hard segment polyester resin, and the preparation steps are as follows:
[0087] 290g neopentyl glycol, 62g ethylene glycol, 597g terephthalic acid and 0.8g monobutyltin oxide were added to a four-necked flask, and a stirring device, a distillation column and a condensation column were set up on the four-necked flask. The temperature was raised to 240°C at a heating rate of 5°C / h under a nitrogen atmosphere. After reaching the set temperature, the temperature was kept for 4h. The sampled resin was clear and bright, with an acid value of 6.4mgKOH / g and a viscosity of 900mPa·s, to obtain a hard segment polyester resin H2
[0088] Example 8
[0089] This embodiment provides a polyester resin for sand-textured powder coatings, and the raw materials and amounts thereof are shown in Table 1:
[0090] Table 1 Preparation raw materials and dosage of polyester resin for sand grain powder coating in Example 8
[0091]
[0092] The preparation steps are:
[0093] Soft segment polyurethane R1 and hard segment polyester resin H2 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin for sand-textured powder coatings.
[0094] Example 9
[0095] This embodiment provides a polyester resin for sand-textured powder coating, and the raw materials and dosages are shown in Table 2:
[0096] Table 2 Preparation raw materials and dosage of polyester resin for sand grain powder coating in Example 9
[0097]
[0098] The preparation steps are:
[0099] Soft segment polyurethane R1 and hard segment polyester resin H1 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin for sand-textured powder coatings.
[0100] Example 10
[0101] This embodiment provides a polyester resin for sand-textured powder coating, and the raw materials and dosages are shown in Table 3:
[0102] Table 3 Preparation raw materials and dosage of polyester resin for sand-textured powder coating in Example 10
[0103]
[0104] The preparation steps are:
[0105] Soft segment polyurethane R2 and hard segment polyester resin H1 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin for sand-textured powder coatings.
[0106] Embodiment 11
[0107] This embodiment provides a polyester resin for sand-textured powder coating, and the raw materials and dosages are shown in Table 4:
[0108] Table 4 Preparation raw materials and dosage of polyester resin for sand-textured powder coating in Example 11
[0109]
[0110] The preparation steps are:
[0111] Soft segment polyurethane R3 and hard segment polyester resin H1 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin for sand-textured powder coatings.
[0112] Example 12
[0113] This embodiment provides a polyester resin for sand-textured powder coatings, and the raw materials and amounts used are shown in Table 5:
[0114] Table 5 Preparation raw materials and dosage of polyester resin for sand-textured powder coating in Example 12
[0115]
[0116]
[0117] The preparation steps are:
[0118] Soft segment polyurethane R4 and hard segment polyester resin H1 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin for sand-textured powder coatings.
[0119] Embodiment 13
[0120] This embodiment provides a polyester resin for sand-textured powder coatings, and the raw materials and amounts used are shown in Table 6:
[0121] Table 6 Preparation raw materials and dosage of polyester resin for sand-textured powder coating in Example 13
[0122]
[0123] The preparation steps are:
[0124] Soft segment polyurethane R5 and hard segment polyester resin H1 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin for sand-textured powder coatings.
[0125] Comparative Example 1
[0126] This comparative example provides a polyester resin, and the raw materials and amounts used for preparation are shown in Table 7:
[0127] Table 7 Preparation raw materials and dosage of polyester resin in comparative example 1
[0128]
[0129] The preparation steps are:
[0130] Soft segment polyurethane R1 and hard segment polyester resin H1 are added to a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator and an antioxidant are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin.
[0131] Comparative Example 2
[0132] This comparative example provides a polyester resin, and the raw materials and amounts used for preparation are shown in Table 8:
[0133] Table 8 Preparation raw materials and dosage of polyester resin in comparative example 2
[0134]
[0135] The preparation steps are:
[0136] The hard segment polyester resin H1 is added into a four-necked flask, and a stirring device, a distillation column and a condensation column are set up on the four-necked flask. In a nitrogen atmosphere, the temperature is raised to 180°C at a heating rate of 5°C / h, and the mixture is kept warm and stirred for 1 hour. Then, an acidolysis agent is added to react, and the temperature is raised to 230°C at a heating rate of 5°C / h, and the mixture is kept warm for 2 hours after reaching the set temperature. Subsequently, the mixture is evacuated at a vacuum degree of -0.09 MPa for 2 hours. Finally, the temperature is lowered to 190°C, a curing accelerator, an antioxidant and a silane coupling agent are added, and the mixture is stirred for 0.5 hours and then discharged to obtain a polyester resin.
[0137] Comparative Example 3
[0138] This comparative example provides a polyester resin, and the raw materials and amounts used for preparation are shown in Table 9:
[0139] Table 9 Preparation raw materials and dosage of polyester resin in comparative example 3
[0140]
[0141] The preparation steps are:
[0142] Add polyol, polyacid, oligomer polyol and catalyst into a four-necked flask, set up a stirring device, a distillation column and a condensation column on the four-necked flask, and in a nitrogen atmosphere, heat up to 240°C at a heating rate of 5°C / h, and keep warm for 4 hours after reaching the set temperature; then cool to 180°C, add an acidolysis agent to react, stir for 1 hour, heat up to 230°C at a heating rate of 5°C / h, and keep warm for 2 hours after reaching the set temperature; then evacuate at a vacuum degree of -0.09MPa for 2 hours; finally cool to 190°C, add a curing accelerator, an antioxidant and a silane coupling agent, stir for 0.5 hours, and then discharge to obtain a polyester resin.
[0143] Comparative Example 4
[0144] This comparative example provides a polyester resin, and the raw materials and amounts used for preparation are shown in Table 10:
[0145] Table 10 Preparation raw materials and dosage of polyester resin in comparative example 4
[0146]
[0147]
[0148] The preparation steps are:
[0149] Add polyol, polyacid and catalyst monobutyl tin oxide into a four-necked flask, set up a stirring device, a distillation column and a condensation column on the four-necked flask, and heat the flask to 240°C at a heating rate of 5°C / h under a nitrogen atmosphere, and keep the temperature for 4 hours after reaching the set temperature; then cool the temperature to 180°C, add polyisocyanate, acidolysis agent and catalyst dibutyltin dilaurate to react, stir for 1 hour, and then heat the flask to 230°C at a heating rate of 5°C / h, and keep the temperature for 2 hours after reaching the set temperature; then evacuate the flask at a vacuum degree of -0.09MPa for 2 hours; finally cool the flask to 190°C, add a curing accelerator, an antioxidant and a silane coupling agent, stir for 0.5 hours, and then discharge the material to obtain a polyester resin.
[0150] Application Example 1
[0151] The polyester resins in Examples 8-13 and Comparative Examples 1-4 were used as raw materials to prepare sand-textured powder coatings. The composition of the sand-textured powder coatings is shown in Table 11 below:
[0152] Table 11 Application Example 1 Sand-textured powder coating components and contents (g)
[0153]
[0154]
[0155] The preparation steps are:
[0156] The prepared raw materials are mixed, tableted by a twin-screw extruder, freeze-crushed, and sieved to obtain sand-textured powder coatings 1-10.
[0157] Application Example 2
[0158] The sand-textured powder coating 1-10 prepared in Application Example 1 was coated on the surface of the aluminum profile by electrostatic spraying, and cured at 160° C. for 15 min to obtain a black sand-textured coating 1-10.
[0159] Performance Testing
[0160] 1. The acid value, viscosity and glass transition temperature of the polyester resins in Examples 8-13 and Comparative Examples 1-4 were tested. The tests were performed with reference to T / GDTL 004-2019. The test results are shown in Table 12.
[0161] Table 12 Test results of acid value, viscosity and glass transition temperature of polyester resin in Examples 8-13 and Comparative Examples 1-4
[0162]
[0163]
[0164] Table 12 shows the test results of the acid value, viscosity and glass transition temperature of the polyester resin in Examples 8-13 and Comparative Examples 1-4. It can be seen from Table 12 that the acid value of the polyester resin for sand-textured powder coatings in Examples 8-13 is 30-40 mgKOH / g, the viscosity at 200°C is 7000-10000 mPa·s, and the glass transition temperature is 65-75°C. The polyester resin has suitable acid value, viscosity and glass transition temperature, which is beneficial to improving the performance of the powder coating.
[0165] 2. The 60° gloss, impact resistance, horizontal flowability, gloss retention after 120℃ / 2h high pressure boiling, color difference ΔE and surface water spot degree of coatings 1-10 in application example 2 were tested, wherein the gloss test was conducted in accordance with GB / T 9754-2007, the impact resistance test was conducted in accordance with T / GDTL004-2019, the horizontal flow was determined according to GB 6554-1986, the water resistance test used the GB 5237.4-2004 standard inner pressure cooker boiling test method, and the "water spot" coverage area of the coating surface after boiling was determined by visual inspection. The test results are shown in Table 13.
[0166] Table 13 Performance test results of coatings 1-10 in application example 2
[0167]
[0168] Table 13 shows the performance test results of coatings 1-10 in Application Example 2. It can be seen from Table 13 that the sand-textured powder coatings prepared with the participation of the polyester resin for sand-textured powder coatings in Examples 8-13, the coatings 1-6 formed by curing after electrostatic spraying, have a 60° gloss of less than 9%, a low gloss, and good impact resistance. After high-pressure boiling in water at 120°C / 2h, the gloss retention rate is ≥94%, and can reach more than 99%, the color difference ΔE≤2, and basically no water spots appear on the surface, indicating that the polyester resin for sand-textured powder coatings provided by the present invention is used to prepare sand-textured powder coatings, and the coatings have excellent sanding effect, water boiling resistance and mechanical properties. When used for surface treatment, the coatings are not easily corroded or scratched, can maintain excellent performance for a long time, and will not affect the appearance.
[0169] No silane coupling agent was added in Comparative Example 1, no soft segment polyurethane was added in Comparative Example 2, and Comparative Examples 3 and 4 were conventional polyester resin formulas, and no hard segment polyester resin and soft segment polyurethane were added. It can be seen that when Comparative Example 1 was used to prepare sand-textured powder coatings, coating 7 had a light retention rate of 92.2% and a color difference ΔE of 1.30 after high-pressure boiling at 120°C / 2h, and there were a large number of water spots on the surface, and the water boiling resistance of the coating was poor; when Comparative Example 2 was used to prepare sand-textured powder coatings, coating 8 had a light retention rate of 88.2% and a color difference ΔE of 1.95 after high-pressure boiling at 120°C / 2h, and there were many water spots on the surface, and the water boiling resistance of the coating was seriously reduced; the sand-textured powder coatings prepared by Comparative Examples 3 and 4 can be regarded as sand-textured powder coatings in the prior art, and it can be seen that compared with the present invention, they have poor water boiling resistance.
Claims
1. A polyester resin for sand-textured powder coating, characterized in that: The invention comprises the following raw materials: a soft segment polyurethane, a hard segment polyester resin and a silane coupling agent; in terms of mass percentage, the soft segment polyurethane comprises the following raw materials: 5-20% of polyisocyanate and 80-95% of oligomer polyol; the hard segment polyester resin comprises the following raw materials: 30-45% of aliphatic polyol and 60-75% of polyacid.
2. The polyester resin for sand-texture powder coating according to claim 1, characterized in that: The polyisocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate and p-phenylene diisocyanate; And / or, the molecular weight of the oligomer polyol is 300-5000 g / mol.
3. The polyester resin for sand-texture powder coating according to claim 1, characterized in that: The aliphatic polyol includes at least one of neopentyl glycol, ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol, hexylene glycol, diethylene glycol, 1,4-cyclohexanediol, 2-methyl-2,4-pentanediol, ethyl butyl propanediol, trimethylolpropane, and pentaerythritol; And / or, the polyacid includes at least one of terephthalic acid, isophthalic acid, trimellitic anhydride, succinic acid, adipic acid, and 1,4-cyclohexane diacid.
4. The polyester resin for sand-texture powder coating according to claim 1, characterized in that: The silane coupling agent includes at least one of bis[3-(triethoxysilyl)propyl]amine and N-[3-(trimethoxysilyl)propyl]ethylenediamine.
5. The polyester resin according to any one of claims 1 to 4, characterized in that The polyester resin also includes the following preparation raw materials: an acidolysis agent, a curing accelerator, and an antioxidant.
6. The polyester resin for sand-texture powder coating according to claim 5, characterized in that: The polyester resin comprises the following raw materials by mass percentage: 1-10% soft segment polyurethane, 80-90% hard segment polyester resin, 0.1-2% silane coupling agent, 1-10% acid hydrolysis agent, 0.01-0.5% curing accelerator, and 0.1-2% antioxidant.
7. The method for preparing the polyester resin for sand-textured powder coating according to claim 6, characterized in that: The following steps are involved: S1, polyisocyanate and oligomer polyol are polymerized to obtain soft segment polyurethane, and aliphatic polyol and polyacid are condensed to obtain hard segment polyester resin; S2, mixing the soft segment polyurethane and the hard segment polyester resin for reaction, adding an acidolysis agent, performing vacuum polycondensation reaction, adding a curing accelerator, an antioxidant and a silane coupling agent, and obtaining the polyester resin for sand texture powder coating.
8. A sand-textured powder coating, characterized in that: A polyester resin for sand-textured powder coating comprising any one of claims 1 to 6; The mass percentage of the polyester resin used in the sand-texture powder coating is 50-60%.
9. A coating, characterized in that: The invention is formed by comprising the sand-textured powder coating according to claim 8.
10. The polyester resin for sand-texture powder coating according to any one of claims 1 to 6, or the use of the sand-texture powder coating according to claim 8 in the surface treatment of aluminum profiles.
Citation Information
Patent Citations
Thermal curable polyester powder coating composition
CN101903480A
Boiling-endurable sand-ripple powder paint for coating corners of aluminum section and preparation method thereof
CN103483988A
Polyester resin composition as well as preparation method and application thereof
CN117866392A
